Omerta - Puzo, Mario (Random House, 2000)
"Don Raymonde Aprile is an old man wily enough to retire gracefully from organized crime after a lifetime of ruthless conquest. Having kept his three children at a distance, he's ensured that they are now respectable members of the establishment. To protect them from harm, and to maintain his entree into the legitimate world of international banking, Don Aprile has adopted a "nephew" from Sicily, Astorre Viola, whose legal guardian made the unfortunate decision to commit suicide in the trunk of a car.".